2015
DOI: 10.1186/s13045-015-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal rearrangement involving 11q23 locus in chronic myelogenous leukemia: a rare phenomenon frequently associated with disease progression and poor prognosis

Abstract: BackgroundProgression of chronic myelogenous leukemia (CML) is frequently accompanied by cytogenetic evolution, commonly unbalanced chromosomal changes, such as an extra copy of Philadelphia chromosome (Ph), +8, and i(17)(q10). Balanced chromosomal translocations typically found in de novo acute myeloid leukemia occur occasionally in CML, such as inv(3)/t(3;3), t(8;21), t(15;17), and inv(16). Translocations involving the 11q23, a relatively common genetic abnormality in acute leukemia, have been seldom reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Indeed, we recently showed that 11q23/MLL rearrangement, a rare minor route cytogenetic change in CML, is associated with poor prognosis. 40 In the current study, we found that 3q26.2 aberration, although regarded as a minor route change, confers a worse prognosis than other ACAs, including trisomy 8, 1 of major route changes. In addition, the concurrent presence of other chromosomal changes in cases with 3q26.2 rearrangements did not affect the survival (Figure 5), indicating the predominant role of 3q26.2 in determining prognosis in these cases.…”
Section: Discussionsupporting
confidence: 46%
“…Indeed, we recently showed that 11q23/MLL rearrangement, a rare minor route cytogenetic change in CML, is associated with poor prognosis. 40 In the current study, we found that 3q26.2 aberration, although regarded as a minor route change, confers a worse prognosis than other ACAs, including trisomy 8, 1 of major route changes. In addition, the concurrent presence of other chromosomal changes in cases with 3q26.2 rearrangements did not affect the survival (Figure 5), indicating the predominant role of 3q26.2 in determining prognosis in these cases.…”
Section: Discussionsupporting
confidence: 46%
“…For instance, chromosome 17, chromosome 3, and complex cytogenetic abnormalities have been associated with worse outcomes, while other abnormalities like deletion of derivative 9 have been shown to have no impact on prognosis when subjected to TKI therapy . Thus, the minor route ACA are not an entirely homogenous group with certain changes such as those involving 11q23 and 3q26 associated with TKI resistance and inferior outcomes . Wang and colleagues proposed a new classification system accounting for the impact of these abnormalities …”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of additional cytogenetic alterations other than t(9;22) is observed in up to 80% of cases of CML‐BP . The most common additional cytogenetic abnormalities include trisomy 8, an extra copy of the Ph chromosome, 3q26 rearrangements, monosomy 7/del(7q), i(17)(q10), trisomy 21, minus Y, and trisomy 19 …”
Section: Introductionmentioning
confidence: 99%